Revealing the diversity of ant-eating spiders in Colombia II: morphology, distribution, and taxonomy of the trilobatus group of the genus Tenedos O. Pickard-Cambridge, 1897 (Araneae: Zodariidae) - Martínez, Leonel; Brescovit, Antonio D.; Martínez, Carlos Prieto (Zootaxa, 2023)
Tenedos O. Pickard-Cambridge, 1897, is the most diverse arrangement of Neotropical zodariids. The genus is composed by several species group, which only the barronus group is formally recognized. However, several groups remain uncharacterized despite being easily distinguishable by the distinctive sexual morphology. We formally proposed a second species group in Tenedos, the trilobatus group, including the known species Tenedos trilobatus Jocqué & Baert, 2002 from Colombia and T. figaro Jocqué & Baert, 2002 from Ecuador, whose type specimens are redescribed herein. Seven new species of the trilobatus group from Colombia are proposed based on both sexes: T. anchicaya sp. n. (♂♀), T. chiribiquete sp. n. (♂♀), T. cumbre sp. n. (♂♀), T. gabi sp. n. (♂♀), T. quimbaya sp. n. (♂♀), T. huila sp. n. (♂♀), T. valle sp. n. (♂♀). New data on the distribution range of Tenedos trilobatus in Colombia are included. We further provide distribution maps and an identification key for all species of the group. Morphological remarks of the new group and a comparison of it with the barronus group are included.